Eco-efficiency assessment of the electricity sector: Evidence from 28 European Union countries - Tenente, Marcos (2020)
This study is aimed at performing the eco-efficiency assessment of the electricity sector in 28 European Union countries. The novelty of our work resides in the combination of Data Envelopment Analysis with Input–Output analysis to perform the eco-efficiency evaluation of the consumption and production supply chains of the electricity sector. According to our findings, the only countries that increased their efficiency scores across all chains of the electricity sector were France (the only efficient country that increased its efficiency), Ireland (the only country that became efficient in all chains), the United Kingdom and Belgium. Additionally, the countries which were efficient across all chains, were France, Luxemburg, Germany, and Sweden while Poland, the Netherlands, Estonia (the only country in the top four lowest efficiency scores in all chains), Hungary, Croatia, Finland, Lithuania, Slovakia, the Czech Republic, Slovenia, and Greece remained inefficient. Overall, it can be concluded that the countries that fostered renewable energy deployment efficiently, gradually decommissioning fossil fuel generation, enhanced their potential in terms of eco-efficiency by reducing the emissions produced by the electricity sector and stimulating the growth of value-added created by it.